Penurunan Konsentrasi Pb dengan Metode Fitoremediasi Menggunakan Tumbuhan Jeringau (Acorus calamus) - Suhar Suhar; Eka Marya Mistar; Ida Hasmita; Nurul Aflah; Ika Rezvani Aprita (Fakultas Teknik, 2023)
Industrial activities have led to the aquatic environment degradation. One of the pollutants is lead (Pb) which has a dangerous toxic effect, cannot be decomposed and is mutagenic. High levels of Pb in waters can result in the death of aquatic biota and pose a threat to human health. This study examined the ability of the Jeringau plant (Acorus calamus) to absorb Pb. The Jeringau plant is taken from the river bank, with a length of 20 cm, has many leaves and roots. Artificial Pb waste was made with various concentrations of 0.5 mg/L, 1 mg/L and 2 mg/L. Furthermore, the Jeringau plant was put into a reactor containing Pb waste and observed for 9 days. The obtained results showed that Pb concentration decreased at the ninth day of 0.03 mg/L, 0.067 mg/L and 0.201 mg/L.